Corrosion of Carbon Steel in Oxygen and NaCl Concentration Cells: the Influence of Solution Temperature and Aeration - Hamad, Muayad F.; Abdul Kader, Huda D.; Alabdly, Hussein A.; Hasan, Basim O.; Ali, Israa S. M. (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Corrosion rate tests were carried out on carbon steel under concentration cells conditions of oxygen and sodium chloride. The effect of aeration in one compartment on the corrosion rate of both coupled metals was determined. In addition, the effects of time and temperatures on the corrosion rate of both coupled metals and galvanic currents between them were investigated. Corrosion potentials for the whole range of operating conditions under concentration cell conditions were also studied. The results showed that under aeration condition, the formation of concentration cell caused a considerable corrosion rate of the Carbon steel specimens coupled in different concentrations of O2 and NaCl due to the galvanic effect. Aerating one compartment caused a noticeable increase in the corrosion rate of the coupled specimen in the other compartment due to the galvanic effect. Increasing temperature caused unstable trends in the free and galvanic corrosion potentials. Increasing the temperature led to an increase in the corrosion rate for both metals.